The Spectator and the Work of Art: Monologues and Dialogues in the 21th Century Museology - Quirosa García, Victoria (Eikón / Imago, 2019)
Contemporary historiography has defined the work of art as an act of communication, which as such needs a transmitter and a receiver, although the guidelines of this dialogue have not always been established. The experience of the spectator in museums has changed in a dizzying way in the second half of the twentieth century, with the demand for a change of attitude that moved from passive contemplation, in a redefinition of the flanêur, to an active role imposed by the own physicality of the work to be experienced. In this text we will reflect on individual cases the coexistence of trends, origin and evolution, to estimate where our steps in the current Museums go, whether the aesthetic experience must change its modus operandi or whether the future of our museology passes through other approaches to the work of art.